2010
DOI: 10.1111/j.1439-0523.2009.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a null allele at the Wx‐A1 locus in durum wheat (Triticum turgidum L. ssp. durum Desf.)

Abstract: With 3 figures and 1 table Abstract This work describes a novel null Wx‐A1 allele detected in one cultivar and two breeding lines from a collection of 48 durum wheats from Argentina. The electrophoretic patterns of waxy proteins showed 45 accessions displaying Wx‐A1 and Wx‐B1 proteins and three accessions that lacked the Wx‐A1 protein. Partial sequence of the Wx‐A1 gene obtained from the three lines lacking the Wx‐A1 protein showed a 1‐bp deletion in exon 6 that produces a frameshift and a premature stop codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Buck Topacio, Vanzetti et al (2010) found that the absence of the Wx-A1 protein in that durum cultivar was associated with a 1-bp deletion in the sixth exon, resulting in a frameshift generating a stop codon. This allelic variant was catalogued as Wx-A1h.…”
Section: Variants Of Wx-a1 Genementioning
confidence: 99%
“…Buck Topacio, Vanzetti et al (2010) found that the absence of the Wx-A1 protein in that durum cultivar was associated with a 1-bp deletion in the sixth exon, resulting in a frameshift generating a stop codon. This allelic variant was catalogued as Wx-A1h.…”
Section: Variants Of Wx-a1 Genementioning
confidence: 99%
“…However, Astrodur did not show this deletion, but the null character is conferred by a single nucleotide deletion in exon-7, which produced a frameshift that generated a premature stop codon in the gene sequence. This mutation is the same as the one described by Vanzetti et al (2010) in the partial sequence of the Wx-A1h allele since the alignment of this partial sequence (458 bp; NCBI ID: GQ120523) shows a 100 % similarity with the Wx-A1 sequence in Astrodur (Fig. 2B), therefore, we classified this allele as putative Wx-A1h.…”
Section: Resultsmentioning
confidence: 94%
“…According to Vrinten et al (1999), null allele Wx-B1b is characterized by the deletion of the entire Wx gene, so the absence of amplicon corresponding to the B genome in cv. Blanqueta when the AFC/AR2 primers were used The asterisks indicate SNPs found in the 3'-UTR region and the arrow a non-synonymous substitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations